(untitled) (Transactions of the Association of European Schools of Planning, 2020)
The impact of European policies strongly depends on their interpretation and application by domestic actors. This is especially true in fields such as European spatial planning and development, which are characterised by informal agreements and fragmented competences. Consequently, EU policies only gain importance if domestic actors consider them relevant and establish links to their respective areas of influence. The European Spatial Development Perspective (ESDP) is often regarded as a success story in European spatial planning and is relatively well known among planners across Europe. The Territorial Agenda documents, often considered successors to the ESDP, have not been met with the same enthusiasm and interest. This contribution uses the concept of storytelling to explain why the ESDP was at least partly successful in appealing to planners. Moreover, it discusses the role and importance of planning education in fostering interest in European spatial development.